Cactus Pear: A Multipurpose Crop and Resilient Feed Source in Dry Environments - Hassan, Sawsan; Louhaichi, Mounir (Alliance Bioversity International-International Center for Tropical Agriculture, 2023)
Cactus pear (Opuntia ficus-indica) emerges as a resilient and multipurpose crop, thriving in harsh environments with minimal inputs and poor-quality soils. This plant, with its adaptability and high water content, offers valuable products for both livestock fodder and human food, contributing to water-scarce regions. The poster addresses the challenge faced by smallholder farmers in semi-arid environments, where limited resources hinder animal feed availability. Leveraging the unique qualities of cactus pear becomes a strategic solution, particularly in North Africa, South Asia, and the Middle East.